PENGARUH PERTUMBUHAN EKONOMI, DANA BAGI HASIL,DAN SISA LEBIH PEMBIAYAAN ANGGARAN TERHADAP PENGALOKASIAN ANGGARAN BELANJA MODAL PADA PEMERINTAH DI PROVINSI BANTEN - Haerul Anwar; Usep Siswadi; Firda Mufidah (The Asia Pacific Journal Of Management Studies, 2023)
This study has a purpose, namely to determine the effect of Economic Growth, Profit Sharing Funds and the Remaining Budget Financing on Budget Allocation in 8 Regencies/Cities in Banten Province in 2016-2020. This research is motivated by the existence of fiscal imbalances between each region and the not yet optimal value of Economic Growth, Profit Sharing Funds and Excess Budget Financing in regions in the Regency / City in Banten Province so that it will affect the value of the Capital Expenditure Budget Allocation. The data used in this study is secondary data sourced from the Central Statistics Agency of Banten Province. The results of the t-count study show that the variable of economic growth and profit sharing has a significant effect. partial effect on capital expenditures, while the remaining over budget financing does not partially affect capital expenditures. The f test shows that all variables have a simultaneous effect. The results showed that economic growth had no effect on capital expenditures, profit-sharing funds had a positive and significant effect on capital expenditures, the remaining excess budget financing had a positive and significant effect on capital expenditures.